Detection of changes in biological characteristics of Aeromonas veronii TH0426 after deletion of lsrB gene by homologous recombination. (January 2023) - Gao, Hongmiao; Wang, Hong; Zhang, Meng; Shan, Xiaofeng; Qian, Aidong; Zhang, Lei; Zhang, Dongxing; Sun, Wuwen
Abstract: Aeromonas veronii is a widespread pathogenic microorganism that can infect humans, animals, and a variety of aquatilia, at the same time, can cause diseases, mainly sepsis and ulcer syndrome. In this research, we first deleted the gene of lsrB 's nucleotide sequences by homologous recombination. The results showed that the median lethal dose (LD50 ) of the mutant strain (Δ lsrB ) for zebrafish was 1.28-times higher than that of the TH0426 strain. The toxicity of TH0426 to epithelioma papulosum cyprini (EPC) cells was 1.15-times and 1.64-times higher than that of Δ lsrB, 1 and 2 h after infection. The production ability of the biofilm of Δ lsrB decreased by 1.38-times, and the adhesion ability of Δ lsrB to EPC cells greatly decreased by 1.96-times than the TH0426. The result of motility detection pointed out that the swimming ability of Δ lsrB was down by 1.67-times. The results indicated that almost all of them lost their flagella after deleting the lsrB gene. In general, the virulence of TH0426 was reduced after deleting the lsrB gene. The final results point out that the lsrB gene of TH0426 is related to motility, biofilm formation, adhesion, and virulence. Highlights: We successfully constructed the lsrB gene deletion strain and the complementation strain for the first time. The virulence of △ lsrB strain were significantly decreased than the wild TH0426 strain.